Students’ Attitude on the Benefits of Project-Based Learning in the Multimodal Platform - Sukiawati Sukiawati; Sitti Nurfaidah (AL LUGHAWIYAAT, 2020)
This study attempts to investigate the benefits of Project-based learning in the multimodal platform. It is exploring students’ perception towards the implementation of Project-based learning (PBL) in the multimodal platform based on students’ experience in working on the project used the multimodal platform in English instructional context. This study adopted a descriptive qualitative method. Data gathered through students’ reflection. The study was conducted in the English Language Education study program, at the University of IAIN Kendari. The participants of this study are fifth-semester students in the academic year of 2019-2020 who taking the Syntax course which the learning process of this course used PBL. Twenty-six students participated in this study by were wrote reflections to obtain information related to their perception toward Project-based learning implementation through the multimodal platform in their classroom. The collected data from students’ reflection then was highlighted, collated, and analyzed through coding and categorization. The results of the research reveal that PBL has advantages to students’ learning process. Besides, this study also shows that students have a positive perception of PBL implementation in the multimodal platform in their English classroom. Thus, this study implies that language teacher and teacher educators could utilize Project-based learning in the multimodal platform as a teaching-learning technic to develop students’ perception as well as students’ performance in the English teaching-learning process.